MODEL PEMBELAJARAN HOTS YANG ADAPTIF TERHADAP PERKEMBANGAN KOGNITIF SISWA SEKOLAH DASAR - Yenny Widyawati; Murfiah Dewi Wulandari; Darsinah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This study aims to explore Higher Order Thinking Skills (HOTS) learning models that are adaptive to the cognitive development of elementary school students. Through literature analysis, this research seeks to discover effective teaching strategies for integrating HOTS into the elementary school curriculum. This study uses a qualitative descriptive method. The data used consists of various HOTS learning models that are adaptive to the cognitive development of elementary school students, obtained through articles and scientific journals. Data collection techniques include literature studies, while data analysis techniques involve reading, observing, and noting. The validity of the data is ensured through theoretical triangulation. The results show that learning models such as Problem-Based Learning (PBL), Project-Based Learning (PjBL), and Discovery Learning are effective in integrating HOTS for elementary school students. PBL emphasizes problem-solving, enhancing students' ability to apply concepts to real-world problems, and developing independent and collaborative learning skills. PjBL focuses on project or product-based outcomes relevant to the teaching material, encouraging students to be active, creative, and innovative. Discovery Learning helps students develop critical and analytical thinking skills through a series of learning stages.